The disease burden of gout in Asian countries and regions from 1990 to 2021, risk factors and forecast analysis: A systematic study of Asian disease burden in 2021 - Fuyu Yang; Runze Chen; Jun Xiong; Wenzhen Wang; Peng Yu; Huilin Wang (PLoS ONE, 2025)
Objective Use the Global Burden of Disease (GBD) database to obtain gout’s disease burden indicators, risk factors, 1990–2021 data in Asian countries/regions and 2050 forecast data for gout prevention and control basis. Methods Collect gout prevalence, incidence etc. from global burden of disease data in Asia, stratified by gender and age, analyze with statistical charts. Use Joinpoint regression model for trend analysis. Predict 2050 East Asia incidence rate with Bayesian Age-Period-Cohort (BAPC) model. Results 1990 - 2021, Age-standardized Prevalence Rate (ASPR) and Age-standardized Incidence Rate (ASIR) rose globally, in Asia and SDI regions. East Asia’s incidence rose fast. Men’s ASPR is nearly three times that of women. 55–59 – year – olds have the highest incidence rate in 2021. High BMI patients are common, and low proportion of kidney dysfunction impairment. East Asia’s ASIR will rise by 2050 but slower. Conclusion Gout’s disease burden rose in Asia 1990–2021. Prevalence and incidence vary by country/region, especially in East Asia. Men’s prevalence is higher. 55–59 – year – olds have the highest prevalence. In Asia’s developed countries, prevalence and incidence are above the global average in 2021. High BMI and kidney dysfunction impairment are key risk factors. These findings necessitate preventive strategies, enhanced cooperation in prevention and control management, public awareness campaigns, and early treatment interventions.